Interactions between brainstem noradrenergic neurons and the nucleus accumbens shell in modulating memory for emotionally arousing events - Kerfoot, Erin C. (Cold Spring Harbor Laboratory Press, 2011)
The nucleus accumbens shell (NAC) receives axons containing dopamine-β-hydroxylase that originate from brainstem neurons in the nucleus of the solitary tract (NTS). Recent findings show that memory enhancement produced by stimulating NTS neurons after learning may involve interactions with the NAC. However, it is unclear whether these mnemonic effects are mediated by norepinephrine (NE) release from NTS terminals onto NAC neurons. The present studies approached this question by examining the contribution of NAC α-noradrenergic receptors in mediating this effect and assessed whether glutamatergic activation of the NTS alters NE concentrations in the NAC. Rats were trained for 6 d to drink from a water spout located at the end of an inhibitory avoidance chamber. On day 7, a 0.35-mA footshock was initiated once the rat approached the spout and remained active until it escaped into the neutral compartment. Blockade of α-noradrenergic receptors in the NAC with phentolamine (0.5 µg/0.5 µL) attenuated memory enhancement produced by glutamatergic (50 ng/0.5 µL) infusion on NTS neurons (P < 0.01). Experiment 2 used in vivo microdialysis to assess whether glutamate activation of NTS alters NAC NE concentrations. NE levels were unchanged by NTS infusion of phosphate-buffered saline (PBS) or low dose glutamate (50 ng/0.5 µL) but elevated significantly (P < 0.05) by combining the same dose with the footshock (0.35 mA, 2 sec) given in Study 1 or infusion of (100 ng/0.5 µL) glutamate alone. Findings demonstrate that NE released from NTS terminals enhances representations in memory by acting on α-noradrenergic receptors within the NAC.